Retrospective and prospectively assessed childhood adversity in association with major depression, alcohol consumption and painful conditions. (31st January 2014) - Patten, S. B.; Wilkes, T. C. R.; Williams, J. V. A.; Lavorato, D. H.; el-Guebaly, N.; Schopflocher, D.; Wild, C.; Colman, I.; Bulloch, A. G. M.
Abstract : Background: Considerable evidence now links childhood adversity to a variety of adult health problems. Unfortunately, almost all of these studies have relied upon retrospective assessment of childhood events, creating a vulnerability to bias. In this study, we sought to examine three associations using data sources that allowed for both prospective and retrospective assessment of childhood events. Methods: Methods. A 1994 national survey of children between the ages of 0 and 11 collected data from a 'person most knowledgeable' (usually the mother) about a child. It was possible to link data for n = 1977 of these respondents to data collected from the same people in a subsequent adult study. The latter survey included retrospective reports of childhood adversity. We examined three adult health outcomes in relation to prospectively and retrospectively assessed childhood adversity: major depressive episodes, excessive alcohol consumption and painful conditions. Results: Results. A strong association between childhood adversities (as assessed by both retrospective and prospective methods) and major depression was identified although the association with retrospective assessment was stronger. Weaker associations were found for painful conditions, but these did not depend on the method of assessment. Associations were not found for excessive alcohol consumption irrespective of the method of assessment. Conclusions: These findings help to allay concerns that associations between childhood adversities and health outcomes during adulthood are merely artefacts of recall bias. In this study, retrospective and prospective assessment strategies produced similar results.